Avaliação biomecânica da influência da microgeometria na osseointegração de implantes instalados em tíbias de ratos expostos à nicotina - Flumian, Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Changes in the macro and microgeometria of dental implants are designed to increase the contact surface of bone-implant and promote osseointegration especially in less dense bone. Thus, this study aims to evaluate biomechanically, the influence of microgeometria in osseointegration of implants placed in the tibia of rats exposed to nicotine or not. Eighty rats were randomly divided into two major experimental groups (n = 40) receiving saline solution (SS) or applications of nicotine (NIC). Thirty days after the start of application, the animals were randomly divided in subgroups (n = 20) which implants (4.0 mm long and 2.2 mm diameter) with different surface treatments made by sandblasting and etching were installed in the surgical alveolus: SS-AC - surface in micrometer scale; Nano-SS - surface at the nanometer scale; NIC-AC - surface in micrometer scale; NIC-Nano - surface at the nanometer scale. Ten animals from each group were euthanized at 30 or 60 days postoperatively. The tibias were submitted to biomechanical evaluation by reverse torque test. Data were statistically analyzed by ANOVA test followed by Tukey posttest (p≤0.05). Nicotine did not reduce the removal torque of titanium implants installed in tibias. At 30 days postoperatively, the SS-AC and AC-NIC groups showed higher removal torque compared to Nano-SS (p≤0.05) group. At 60 days postoperatively, the SS-AC group had a higher removal torque compared to the NICNano (p≤0.05) group. Within the limits of the present study, it was concluded that nicotine does not reduce the removal torque of the implants placed in the tibia of rats, suggesting that it does not influence the osseointegration process, while the surface micrometer scale increased the removal torque of the implants installed in the tibia of rats modified or not by nicotine

As modificações na macro e microgeometria dos implantes dentários têm por objetivo aumentar a superfície de contato osso-implante e favorecer a osseointegração principalmente em osso menos denso. Assim, o presente estudo tem por objetivo avaliar, biomecanicamente, a influência da microgeometria na osseointegração de implantes instalados em tíbias de ratos expostos ou não à nicotina. Oitenta ratos foram distribuídos aleatoriamente em dois grandes grupos experimentais (n=40) submetidos a aplicações de solução salina (SS) ou de nicotina (NIC). Após 30 dias do início das aplicações, os animais foram aleatoriamente distribuídos em subgrupos (n=20) onde implantes (4,0 mm de comprimento e 2,2 mm de diâmetro) de diferentes tratamentos de superfície confeccionados por meio de jateamento e ataque ácido foram instalados no alvéolo cirúrgico: SS-AC - superfície em escala micrométrica; SS-Nano - superfície em escala nanométrica; NIC-AC - superfície em escala micrométrica; NIC-Nano - superfície em escala nanométrica. Dez animais de cada grupo foram eutanasiados aos 30 e 60 dias pósoperatórios. As tíbias foram submetidas avaliação biomecânica pelo teste de torque reverso. Os dados obtidos foram submetidos à análise estatística pelo teste ANOVA seguido pelo pós-teste de Tukey (p≤0,05). A nicotina não reduziu o torque de remoção de implantes de titânio instalados em tíbia de ratos. Aos 30 dias pósoperatórios, os grupos SS-AC e NIC-AC apresentaram maior torque de remoção em relação ao grupo SS-Nano (p≤0,05). Aos 60 dias pós-operatórios, o grupo SS-AC apresentou maior torque de remoção em relação ao grupo NIC-Nano (p≤0,05). Dentro dos limites do presente estudo, concluiu-se que a nicotina não reduz o torque de remoção dos implantes instalados em tíbia de ratos, sugerindo que ela não interfere no processo...
Keywords: Implantes dentários; Osseointegração; Nicotina; Biomecânica; Dental implants